1996
DOI: 10.1021/jp952743q
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model Indicating the Origin of the Angular Momentum Gap Law in Rotational Transfer

Abstract: In the recently proposed angular momentum (AM) theory of collision-induced rotational transfer, the probability distribution of effective impact parameter (or torque arm) plays a central role as the means via which linear momentum is converted to AM. This was found empirically to be best represented by the function P(b n ) ) b n -γ . Here we show that the ubiquitous inverse power function is readily explained as resulting from the combined contributions to P(b n ) that come from considering both angular and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…15 and Osborne et al 34 have demonstrated that the above expression predicts an exponential-like fall of RT crosssections with increasing Dj. These two articles also stress the importance of the range of integration over effective impact parameter to the state-to-state probability, i.e.…”
Section: Kinematic Relationshipsmentioning
confidence: 91%
See 3 more Smart Citations
“…15 and Osborne et al 34 have demonstrated that the above expression predicts an exponential-like fall of RT crosssections with increasing Dj. These two articles also stress the importance of the range of integration over effective impact parameter to the state-to-state probability, i.e.…”
Section: Kinematic Relationshipsmentioning
confidence: 91%
“…The form of P(b n ) obtained from analysis of extensive RT data, quite accurately follows a b n Àg dependence in the case of pure RT 15 and was shown to represent the probability density of the repulsive anisotropy of a typical atom-diatom intermolecular potential. 34 Note that here and in other publications we use the expression P(b n ) as shorthand for P(b perp n ,cos f) where b perp n is the effective impact parameter generated by the perpendicular component of incident relative momentum and f is the angle this momentum subtends to the normal. 34 Both elements contribute to the b n Àg form of P(b n ) that gives RT its characteristic inverse power dependence on transferred AM, 34 a shape referred to here as exponential-like to provide an easily visualised description.…”
Section: Kinematic Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include rotational transfer (RT) [24,26,36,[38][39][40], i.e., state change within a vibrational manifold, vibration-rotation transfer (VRT) [41,42], i.e., transitions between vibrational states and electronic energy transfer [43], i.e., transitions between discrete levels of different electronic states. An example is given in Fig.…”
Section: Pðdj; Deþmentioning
confidence: 99%